Implementation of Monitored Anaesthesia Care (MAC) in MRI Pediatric Examinations: A Review of Procedures and Side Effects - HIDAYAT, FATHUR RACHMAN; PRANANDYA, BRIAN ILHAM (Journal of Applied Health Management and Technology, 2025)
Magnetic Resonance Imaging (MRI) in pediatric patients presents significant challenges due to the difficulty children often experience in remaining still and cooperative during the procedure. Monitored Anesthesia Care (MAC) is frequently employed to address these challenges, ensuring both patient comfort and optimal imaging quality.This study aims to provide a detailed overview of the procedural protocol and potential adverse effects associated with the use of MAC in pediatric MRI examinations. A qualitative descriptive analysis was conducted based on a clinical case from the radiology department of a tertiary care hospital in Indonesia, supported by relevant literature review. Key procedural steps include pre-procedure assessment, laboratory testing, intravenous line placement, sedation administered and monitored by an anesthesiologist, continuous vital signs monitoring, airway management, and post-anesthesia recovery. Potential complications identified include allergic reactions to gadolinium-based contrast agents, local injection site bruising, hypothermia, airway obstruction, laryngospasm, post-sedation agitation, confusion, respiratory depression, and heightened anxiety due to the confined MRI environment. The report highlights the necessity of strict adherence to safety protocols, comprehensive patient preparation, and the availability of emergency equipment and trained personnel to mitigate risks. In conclusion, the use of MAC in pediatric MRI is a safe and effective strategy when performed with proper planning and multidisciplinary collaboration, enhancing diagnostic accuracy and patient safety.